Avaliação da sincronia rítmica em crianças com transtorno do espectro do autismo em atendimento musicoterapêutico - Renato Tocantins Sampaio (2015)
The Autism Spectrum Disorder (ASD) is a developmental disorder with early beginning and non-degenerative chronic course, with heterogeneous impact on various areas of development, especially on social interaction, verbal and non-verbal communication and behavior, with the presence of limited or stereotyped patterns of behavior and interests. In recent decades, studies in Neurosciences have sought to understand and describe how musical is processed in the nervous system in people with or without ASD. Music Therapy is a systematic process of intervention in which the therapist helps the patient to promote health using musical experiences and the relationships that emerge as dynamic forces of change, with music therapy services with people with ASD being largely widespread in Brazil and other countries. Research in Music Therapy has shown the efficacy of some evidence based clinical models, especially regarding the abilities of social interaction and communication. Nevertheless, there is a hiatus in the literature about quantitative evaluations of the clinical process. This PhD Thesis at the Neurosciences Program at Federal University of Minas Gerais (UFMG) is embedded in a broader research project entitled Rhythmic Synchrony and Social Interaction in Autism, registered at Plataforma Brasil with the number CAAE 17568513.0.0000.5149, which aims to develop systematic models to measure clinical evolution of children with ASD during music therapy treatment. The goal of this thesis was to develop of the Rhythmic Synchrony in Music Therapy Evaluation Protocol (PSinc) and to conduct initial studies of reliability, structural validity and application to clinical context. Four studies were performed. The first study is a literature review in which researches in neurosciences, especially in neurosciences of music, serve as a foundation for new considerations about music therapy clinical practice with people with ASD. The second study addresses the reliability of the Rhythmic Synchrony in Music Therapy Evaluation Protocol. Twenty video clips randomly selected from music therapy clinical processes of children with ASD were analyzed by six judges (two inclusive education teachers and four music therapists). The data analysis supports the protocols internal consistence: 56% of correlations showed 0.71 or higher scores and Cronbachs Alpha was 0.85. All polychoric correlations in interjudges evaluations have high values, above 0.71. The correlations between the researcher and each judge were equal or above 0.7 in approximately 63% of the cases. Kendalls K level of accordance was 0.66, suggesting that a specific training for using PSinc is needed. In the third study 758 sequences of a music therapy single case were evaluated by a dynamic confirmatory factor analysis in order to verify the structural validity of the Rhythmic Synchrony in Music Therapy Evaluation Protocol. A factorial model of one general latent factor with a lag showed a god adjustment to the data (X2=719.12, dF=177, p<0.001, CFI=0.985, RMSEA=0.064 with 90% confidence interval of 0.059-0.068 and p<0.01), suggesting a valid protocol to measure the ability to synchronize and stay synchronized. The forth study addressed the application of the PSinc to eight sessions of a single case process of a child with Autism Spectrum Disorder in a music therapy clinical process to examine if the ability to Rhythmic Synchronize was developed. The analyses of the protocol application showed internal consistence of data with Cronbach´s Alpha=0.84, IC(95%)=0.82-0.87 e standard deviation=0.31. The temporal series of the ability to Rhythmic Synchronize adjusted to a stationary model (X2=67.887, dF=64 and small residuals autocorrelations) suggesting that the ability was not developed during this period. The Rhythmic Synchrony in Music Therapy Evaluation Protocol may be considered a evaluation instrument with satisfactory reliability, consistent structural validity and utility to estimate clinical improvement of children with ASD during music therapy clinical processes. Nevertheless, further studies are needed regarding concurrent, construct and predictive validity and more efforts have to be undertaken to enhance the protocol reliability.